A Comparison of Coping Styles of Mothers of Exceptional Children with Mothers of Normal Children - Mahnaz Aliakbari-Dehkordi; Ali asghar Kako-Joibari; Tayyebeh Mohtashami (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: The aim of this study was to compare coping styles of mothers of exceptional children with each other and with mothers of normal children. Materials & Methods: The study was a Causal-Comparative research. Sample size of 120 mothers in four groups of mental retardation, low vision, hearing impairment and normal children randomly clustered chosen in the city of Karaj. In this study coping styles questionnaire (Lazarus and Folkman, 1998) was used. Data were analyzed through descriptive statistics, multivariate analysis of variance and pos hoc Tukey test. Results: The results showed that there is significant difference (P<0.05) in applying coping styles of "distancing, accepting responsibility, escape-avoidance and positive reappraisal", between mothers of exceptional children and mothers of normal children. Also, this study showed that there are differences among mothers of exceptional children that these differences are more for mothers of hearing impairment children. Conclusion: Since mothers of exceptional children differ from each other and mothers of normal children in applying coping styles, recommended to liable and professionals are active in this area to educate proper solutions to parents of exceptional children especially mothers to cope with stress. With more education and support, mothers can cope with life stresses more suitable and family will be benefited from higher mental calmness.